Academic Education in Complementary Medicine: A Tuscan Methodological Perspective. (2007) - Gensini, Gian Franco; Conti, Andrea A.
Abstract : The implementation of complementary medicine (CM) involves a large number of persons in Italy, and in the nineties, the percentage of Italian citizens adopting the most frequent and relevant practices of CM almost doubled. Appropriate academic education in CM is an important and fascinating challenge for current didactic systems in the Italian University. Already in 2004, the Joint Italian Conference of the Deans of the Faculties of Medicine and of the Presidents of Medical Degree Courses released an official statement regarding the relationship between CM and health area degree courses. The main teaching objectives embedded in the institutional framework proposed by the Joint Italian Conference are now finding specific implementation modalities in the University of Florence. For many years, the Florence Medical School has had strong and fruitful contacts with institutional bodies in Tuscany and, together with these institutions, has established a continuous dialogue with the world of CM. This exchange has given rise to various teaching activities within the academic setting. With specific reference to the undergraduate curriculum in Medicine and Surgery, a methodological course regarding CM has been designed and conducted, with selective attention being given to the CM practices having an enhanced rate of supportive scientific evidence, such as herbal medicine and acupuncture. With regard to the postgraduate curriculum, a Master degree in Acupuncture and Traditional Chinese Medicine and a Master in Clinical Phytotherapy are already active in the University of Florence and are having a remarkable success among the attending health professionals. This high degree of satisfaction well documents the importance, need and feasibility of structured academic education in CM and, in particular, of a methodological didactics such as those currently implemented in the Florence Medical School.